TEACHING SPEAKING BY USING AUSTRALIA – ASIA DEBATE STRATEGY AT SENIOR HIGH SCHOOL - Solihati Solihati; Don Narius (Journal of English Language Teaching, 2016)
Speaking is a basic skill that should be mastered by students besides the other skills. However, they find difficultes to speak English. it is caused lack sel-self confident, lack vocabulary, they are difficult to pronounce the words, they have interest to learn English. Therefore, the writer chooses Australia - Asia Debate strategy as a form of speaking practice to encourage students to be active, and confident in a discussion. So, they accustomed to express their ideas in English. In Australia - Asia Debate strategy, students are divided in two teams. They discuss the topic that is given by the teacher. The first team agrees with the topic and the second team disagrees about the topic. Each of team is given an opportunity to tell their ideas and responds the other arguments. By using this strategy, students are expected to improve their ability in speaking.